2H-1,4-Benzoxazin-3(4H)-one linked 1,2,3-triazole derivatives and their study on inducing DNA damage in tumor cells - Hou, Xixi; Guo, Yajie; Wang, Xi; Gao, En; Yang, Jianxue (Frontiers in Pharmacology, 2025)
This study explores the anticancer potential of rigid planar compounds capable of intercalating into tumor cell DNA, thereby inducing DNA damage and subsequent cell death. A novel series of compounds (c1–c20) were synthesized using 2H-1,4-benzoxazin-3(4H)-one as the planar core structure, with 1,2,3-triazole groups introduced at the 7-position. Biological evaluation across multiple human tumor cell lines revealed that several c-series compounds exhibited notable inhibitory activity against Huh-7 liver cancer cells, with IC50 values of 28.48 μM (c5), 32.60 μM (c14), 31.87 μM (c16), and 19.05 μM (c18). Mechanistic studies indicated that these compounds effectively induced DNA damage, as evidenced by the upregulation of γ-H2AX, and triggered apoptosis via increased caspase-7 expression. Moreover, enhanced LC3 expression and autophagosome formation suggested the activation of autophagy pathways. The observed biological activities are likely attributed to the rigid planar configuration of the molecules, which facilitates DNA intercalation. Collectively, these results highlight the potential of these synthesized compounds as promising lead candidates for the development of novel therapeutic agents against liver cancer. Importantly, acute toxicity studies in mice demonstrated that these compounds possess favorable safety profiles, further supporting their potential for future preclinical development.